2021
DOI: 10.1111/tbed.13964
|View full text |Cite
|
Sign up to set email alerts
|

Detection of African swine fever virus in free‐ranging wild boar in Southeast Asia

Abstract: African Swine Fever (ASF) is a highly contagious and fatal viral disease affecting both domestic and wild suids. The virus was introduced to Southeast Asia in early 2019 and has since spread rapidly throughout the region. Although significant efforts have been made to track and diagnose the disease in domestic pigs, very little is known about ASF in free‐ranging wild boar and their potential role in maintaining the disease within Southeast Asia. Through a collaboration between government and non‐government act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Wild boar and feral pigs are a possible source of the ASFV outbreak described, as in European outbreaks, however current literature suggests this to be unlikely in Lao PDR (Denstedt et al., 2020 ). Spread of this nature would require prior evidence of ASFV circulating in wild boar populations over enough time for the disease to spread over large distances (Boklund et al., 2020 ; Schulz et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wild boar and feral pigs are a possible source of the ASFV outbreak described, as in European outbreaks, however current literature suggests this to be unlikely in Lao PDR (Denstedt et al., 2020 ). Spread of this nature would require prior evidence of ASFV circulating in wild boar populations over enough time for the disease to spread over large distances (Boklund et al., 2020 ; Schulz et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important transmission routes for ASFV introduction from the wild reservoir to pig holdings in Belgium, and between holdings, have been identified based on questionnaire surveys (Mauroy et al, 2021). As reported in this Special Issue, ASFV infection in wild boar in Southeast Asia has been confirmed for the first time, the result of a probable viral spillover from domestic pigs (Denstedt et al, 2021). In another article, O'Neill et al (2021) investigate whether ASFV can potentially regulate wild boar density.…”
mentioning
confidence: 99%
“…A recently published study has found several ASFV-positive wild boar carcasses in Laos and Vietnam ( 26 ). These results suggest that these two countries are likely to have a large ASFV-infected wild boar population, which coincides with our results as they are also medium-risk countries (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%